Pengaruh Atmosphere Museum dan Event Marketing terhadap Keputusan Berkunjung Ulang Wisatawan Museum Angkut Kota Wisata Batu - BUDI SANTOSO; Agus Widarko; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstractThe research purpose is to know and analyze the influenceatmosphere museum and event marketing simultaneously and partially on tdecision travelers visiting Museum Angkut. The sampling technique uspurposive sampling, that the consideration of certain criteria. Data analysis toused in this research is Multiple Linear Regression Analysis.Based on the results of this research note that the value of Fcount 77.6853.09 Ftable so it can be concluded that the Atmosphere museum and EventMarketing influence simultaneously decision to visit again the tourists.Atmosphere Museum and the variable of 7.202 tcount > ttable of 1.98472 andvariable Event Marketing tcount of 7.394> ttable of 1.98472, which meansAtmosphere Museum and Event Marketing partial effect to the decision to visitagain the tourists Museum Angkut.Keywords: Atmosphere Museum, Event Marketing and Decision Visiting